Middle Cerebral Artery Pulsatility Index as Predictor of Cognitive Impairment in Hypertensive Patients - Harris, Salim; Reyhan, Teuku; Ramli, Yetty; Prihartono, Joedo; Kurniawan, Mohammad (Frontiers in Neurology, 2018)
Background: Cognitive impairment is a manifestation of cerebrovascular disease regarding hypertension and other degenerative diseases which has become a global health issue due to increased life expectancy. Recently, the gold standard used for diagnosing vascular cognitive impairment (VCI) has required a combination of the neurophysiological approach and magnetic resonance imaging (MRI). The Neurosonological approach, involving measuring the pulsatility index (PI) of the middle cerebral artery (MCA) using Trans Cranial Doppler (TCD), can hopefully be used as an affordable alternative predictor of VCI in patients with hypertension. Methods: A cross-sectional study was conducted at the Outpatient Clinic of the Department of Neurology in Ciptomangunkusumo Hospital, Jakarta. Sixty-six hypertensive subjects with no macrovascular complication were selected and screened using the Montreal Cognitive Assesment-Indonesia version (MoCA-Ina) to determine their cognitive status. Subjects were categorized into two groups; subjects with scores ≥26 were classified as the normal cognitive group, while subjects with scores <26 were classified as the cognitive impairment group. Both groups then underwent TCD examination to determine bilateral MCA PI. Results: There was a significant difference between MCA PI in both groups; it was higher in the cognitive impairment group than normal group (p < 0.001). Subjects with an increased left MCA PI were more likely to suffer cognitive impairment than those with an increased right MCA PI. Conclusion: MCA PI can be used as a predictor for cognitive impairment in hypertensive subjects.